2013
DOI: 10.1159/000363193
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Outcome of Traumatic Extra-Axial Hematomas Causing Brain Herniation in Children

Abstract: Aim: The aim of this study was to assess the surgical outcome and prognostic importance of clinical and radiological data from children operated on under emergency conditions due to an extra-axial hematoma causing brain herniation. Methods: This retrospective study included 25 children operated on due to herniated traumatic extra-axial hematomas from January 2000 to December 2010. Results: Of those 25 children, 17 (68%) were diagnosed with subdural hematoma (SDH), 7 (28%) with epidural hematoma (EDH) and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…5,6 The authors investigating the patients operated on due to extra-axial hematoma also found an important impact of GCS and the pupil response on the outcome. 8,14,15 Our study confirmed this result in both groups. Dysautonomia or autonomic dysfunction is a condition in which the autonomic nervous system does not work properly.…”
Section: Physiological Factorssupporting
confidence: 88%
See 2 more Smart Citations
“…5,6 The authors investigating the patients operated on due to extra-axial hematoma also found an important impact of GCS and the pupil response on the outcome. 8,14,15 Our study confirmed this result in both groups. Dysautonomia or autonomic dysfunction is a condition in which the autonomic nervous system does not work properly.…”
Section: Physiological Factorssupporting
confidence: 88%
“…The authors studying patients with EDH and SDH found a poorer outcome associated with a greater midline shift and the thickness of hematoma. 14,15,31 Our analysis confirms these relationships. Similarly, the greater the thickness of hematoma is, the worse the prognosis in the EDH and SDH groups is.…”
Section: Computer Tomography (Ct) Scans Characteristicssupporting
confidence: 82%
See 1 more Smart Citation
“…We also noted that the postoperative recovery was better in patients with high GCS scores. The evaluation of the patients who underwent surgery revealed that the median GCS scores of those who died and who survived following surgery were 6 (4-12) and 12 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), respectively; the difference was statistically significant (p < 0.001). Araujo et al (2012) reported that the primary location was the temporoparietal region in 26.5% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of radiological features is often helpful in determining the necessity to decompress. Midline shift of the brain on computed tomography (CT) is highly prognostic in children with the degree of shift being inversely related to outcome [ 33 ]. Interestingly, in adults, where an absence or compression of the basal cisterns is predictive of poor outcome [ 34 ], in the paediatric population, patent basal cisterns do not exclude high ICP [ 35 ] and extra caution should be observed (Fig.…”
Section: Indicationsmentioning
confidence: 99%